Influence of Abscisic Acid and Sucrose on Somatic Embryogenesis in Cactus Copiapoa tenuissima Ritt. forma mostruosa - J. Lema-Rumińska; K. Goncerzewicz; M. Gabriel (The Scientific World Journal)
Having produced the embryos of cactus Copiapoa tenuissima Ritt. forma monstruosa at the globular stage and callus, we investigated the effect of abscisic acid (ABA) in the following concentrations: 0, 0.1, 1, 10, and 100 μM on successive stages of direct (DSE) and indirect somatic embryogenesis (ISE). In the indirect somatic embryogenesis process we also investigated a combined effect of ABA (0, 0.1, 1 μM) and sucrose (1, 3, 5%). The results showed that a low concentration of ABA (0-1 μM) stimulates the elongation of embryos at the globular stage and the number of correct embryos in direct somatic embryogenesis, while a high ABA concentration (10–100 μM) results in growth inhibition and turgor pressure loss of somatic embryos. The indirect somatic embryogenesis study in this cactus suggests that lower ABA concentrations enhance the increase in calli fresh weight, while a high concentration of 10 μM ABA or more changes calli color and decreases its proliferation rate. However, in the case of indirect somatic embryogenesis, ABA had no effect on the number of somatic embryos and their maturation. Nevertheless, we found a positive effect of sucrose concentration for both the number of somatic embryos and the increase in calli fresh weight.